Konstruksi Media Online Detik.com dan Kompas.com terhadap Vanuatu - Fikri Ali Kurnia; Shulfi Ana Helmi; Sunnah Dwi Rochmana (Program Studi Ilmu Komunikasi FBIK Unissula, 2021)
Vanuatu is one of the Pacific Island countries that consistently raises the issue of alleged human rights violations in Papua at every opportunity at the UN session. On September 27, 2020, Vanuatu, represented by the Prime Minister of the Republic of Vanuatu, Bob Loughman, returned to address the issue related to human rights violations of the Papuan at the 75th UN session. Vanuatu's statement and its reply from the Indonesian diplomat, Sylvany Austin Pasaribu, at the 75th UN session became the spotlight of various media. Detik.com and Kompas.com as online media pioneers and one of the most frequently accessed news sites, were also reported that occurrence. This research aims to find out the differences between those media on packaging its report of Vanuatu after the issue of Papuan human rights violations was raised at the 75th UN General Assembly. The news period under research is from 27 September to 2 October 2020. This research uses qualitative research method with the Zhongdang Pan and Gerald M Kosicki framing analysis model. In this research, Detik.com was more likely to corner Vanuatu. This matter can be seen in terms of quantity and packaging of news. Meanwhile, Kompas.com, didn't put Vanuatu in an advantageous position, but was trying to show balance in its report.